TELAAH ULANG MANHAJ TAHLILI (TAFSIR ANALISIS) - Anieg, Muhammad (Kopertais Wilayah X Jawa Tengah, 2014)
Tafsir is the main instrument in an attempt to answer the problems of theÂ people, who must soon discovered the concept or theory. This departs from theÂ question that is often uttered by Hassan Hanafi: